(untitled) ("Conference on Universal Science Research 2023", 2023)
The syllabic structure of English words refers to the organization of sounds within a word into distinct units known as syllables. A syllable is a unit of sound that contains a single vowel sound and may be composed of one or more consonant sounds. Understanding the syllabic structure of English words is important for language learners and can help improve pronunciation and fluency.